Investigating autonomic dysfunction in post-COVID-19 syndrome from skin to brain: A case-control study using EMG-SSR and fNIRS - Jia-Yin Ma; Jia-Jia Wu; Yi Zhu; Mou-Xiong Zheng; Xu-Yun Hua; Jian-Guang Xu (Brain Research Bulletin)
Background: Autonomic dysfunction is a well-recognized complication associated with post-COVID-19 syndrome (PCS). ANS maladaptation could underlie a potential pathogenetic mechanism of PCS, contributing to PCS symptoms. However, there remains an ongoing debate regarding whether autonomic and neuropathic symptoms observed in PCS patients are indicative of central or peripheral ANS pathology. The purpose of this study is to investigate both the central and peripheral nervous systems of ANS in patients with PCS. Methods: We evaluated the integrity of the peripheral ANS using sympathetic skin response (SSR) and examined the central ANS using functional near-infrared spectroscopy (fNIRS) covering the fronto-parietal cortex in PCS patients (n = 7) and matched healthy controls (n = 7). Functional connectivity, topological parameters of fNIRS brain network were analyzed. To compare the SSR and fNIRS parameters between patients and age-matched healthy controls, Mann-Whitney U tests were performed for each parameter separately. The AUC of each topological metric of fNIRS network was utilized as a statistical scalar for comparison. To characterize the correlation between SSR and significantly different topological metrics of fNIRS network, Spearman correlation analysis was performed. Results: The latencies of palmar SSR were significantly prolonged in the patients with PCS than the controls (p < 0.05). 34 functional connections showed a significant increase (p < 0.05, uncorrected). Regional nodal properties revealed that the fronto-parietal networks of PCS patients had a higher degree in primary somatosensory cortex (S1) (p < 0.001, corrected) and motor cortex, a lower node efficiency in dorsolateral prefrontal cortex (DLPFC), and a higher efficiency in S1 (p < 0.05, uncorrected). Latencies of palmar SSR were significantly positively correlated with zFC within sensorimotor cortex, and node efficiency/degree of S1 (p < 0.01). Amplitudes of palmar and plantar SSR were significantly positively correlated with node efficiency of DLPFC (p < 0.05). Conclusions: Our findings suggest that there were alternations in both central and peripheral parts of ANS in PCS patients. These preliminary results indicate that PCS may lead to changes in both the peripheral and central aspects of ANS, which would help to extend the understanding of the role of the ANS in PCS, offering new perspectives on evaluation and treatment. Trial registration: This study has been registered with the Chinese Clinical Trial Registration Center (registration number: ChiCTR2200064342; registration date:2022/10/3)